Associated data for 'Printed borders for sixteenth-century music or music paper and the early career of music printer Thomas East', the library - Butler, K (University of Oxford, 2017)
Data set created from the works available on Early Music Online in December 2015 and produced for the article, 'Printed Borders for Sixteenth-Century Music or Music Paper and the Early Career of Music Printer Thomas East', The Library, forthcoming 2017/18. Two versions of the data are supplied - one in .xlsx and the other in .xml.